Enhancing The Performance and Sustainability of Lightweight Hebel Bricks Using Local Coco Fiber Additives: A Green Material Innovation for Circular Construction - Don R. G. Kabo; Tumpu, Miswar; Denny B. Pinasang; Carter Kandou; Herman Tumengkol; Hoong-Pin Lee (International Journal of Computational and Experimental Science and Engineering, 2026)
The construction industry faces increasing pressure to adopt sustainable and low-carbon materials, particularly in the production of lightweight concrete such as Hebel bricks. This study investigates the incorporation of locally sourced coco fibre, an agricultural waste derived from coconut husks, as a natural additive in Hebel brick mixtures. The novelty of this research lies in the utilization of coco fibre—abundant, biodegradable, and mechanically resilient—as both a performance-enhancing component and an ecological solution for Indonesia’s construction sector. By improving the mechanical properties of lightweight bricks while promoting resource circularity, this approach contributes to green material innovation and addresses waste valorisation challenges in coconut-producing regions such as North Sulawesi. An experimental method was employed using five mix proportions with coco fibre contents of 0% (control), 0.5%, 1.0%, 1.5%, and 2.0%. Compressive strength and flexural strength tests were conducted in accordance with ASTM C109 and ASTM C348, respectively, at curing ages of 3, 7, and 28 days. The results demonstrate that compressive strength increased significantly with coco fibre addition up to an optimal content of 1.5%. At 28 days, the optimal mixture achieved a compressive strength of 3.42 MPa, exceeding the minimum requirement of 3 MPa specified by SNI 03-0349-1989 for lightweight concrete blocks. Furthermore, the bulk density of all mixtures remained below 1,000 kg/m³, confirming their suitability for non-structural lightweight construction applications. Overall, this study confirms that coco fibre incorporation enhances mechanical performance while supporting sustainable construction practices, circular economy principles, and the development of environmentally responsible building materials.